Low-Cost, High-Performance Spray Pyrolysis-Grown Amorphous Zinc Tin Oxide: The Challenge of a Complex Growth Process - Caffrey, David; Shvets, Igor (My University, 2020)
Transparent conductive oxides (TCOs) are important materials for a wide range of optoelectronic devices. Amorphous zinc tin oxide (a-ZTO) is a TCO and one of the best nontoxic, low-cost replacements for more expensive amorphous indium-gallium-zinc oxide. Here, we employ spray pyrolysis (SP), an inexpensive and versatile chemical vapor deposition-based technique, to synthesize a-ZTO with an as-deposited conductivity of ≈300 S/cm—the highest value hitherto among the reported solution-processed films. Compositional analysis via X-ray photoelectron spectroscopy reveals a nonstoichiometric transfer of Zn and Sn from the dissolved precursors into the film, with the best electrical properties achieved at a film composition of xfilm = 0.38 ± 0.04 ((ZnO)x(SnO2)1–x (0 < x < 1)). The morphology of these films is compared to films synthesized by physical vapor deposition (PVD), and a strong correlation between morphology and electrical properties is revealed. The granular nature of the SP-grown films, which seems like a drawback at first glance, brings about the prospect of using a-ZTO in ink-jet-printed films from a nanoparticle suspension for the room-temperature deposition. Brief post-anneal cycles in N2 gas improve the conductivity of the films by means of grain boundary (GB) passivation.
PUBLISHED
Keywords: Zinc Tin Oxide; Spray Pyrolysis; Transparent Conducting Oxides; XPS; TCO; Amorphous oxide semiconductor; Zinc tin oxide; ZTO; Spray pyrolysis; X-ray photoelectron spectroscopy